Death and redemption : the Gulag and the shaping of Soviet society - Barnes, Steven Anthony (Princeton, N.J. : Princeton University Press, 2011)
Death and Redemption offers a fundamental reinterpretation of the role of the Gulag--the Soviet Union's vast system of forced-labor camps, internal exile, and prisons--in Soviet society. Soviet authorities undoubtedly had the means to exterminate all the prisoners who passed through the Gulag, but unlike the Nazis they did not conceive of their concentration camps as instruments of genocide. In this provocative book, Steven Barnes argues that the Gulag must be understood primarily as a penal institution where prisoners were given one final chance to reintegrate into Soviet society.
The origins, functions, and institutions of the Gulag -- Reclaiming the margins and the marginal : Gulag practices in Karaganda, 1930s -- Categorizing prisoners : the identities of the Gulag -- Armageddon and the Gulag, 1939-1945 -- A new circle of hell : the postwar Gulag and the rise of the special camps -- The crash of the Gulag : releases and uprisings in the post-Stalin era.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Glavnoe upravlenie ispravitelʹno-trudovykh lagereĭ OGPU -- History; GULag NKVD -- History; Glavnoe upravlenie ispravitelʹno-trudovykh lagereĭ OGPU; GULag NKVD; Internment camps -- Soviet Union -- History; Internment camps -- Social aspects -- Soviet Union -- History; Prisons -- Soviet Union -- History; Prisons -- Social aspects -- Soviet Union -- History; Political prisoners -- Soviet Union -- Social conditions; Prisoners -- Soviet Union -- Social conditions; Forced labor -- Social aspects -- Soviet Union -- History; Soviet Union -- Social conditions; Electronic books; Camps d'internement -- URSS -- Histoire; Camps d'internement -- Aspect social -- URSS -- Histoire; Prisons -- URSS -- Histoire; Prisons -- Aspect social -- URSS -- Histoire; Prisonniers politiques -- URSS -- Conditions sociales; Prisonniers -- URSS -- Conditions sociales; Travail forcé -- Aspect social -- URSS -- Histoire; URSS -- Conditions sociales; Livres numériques.; e-books.; SOCIAL SCIENCE -- Penology; Internment camps; Internment camps -- Social aspects; Prisoners -- Social conditions; Prisons; Prisons -- Social aspects; Social conditions; Soviet Union; Electronic books; dissertations; History; Academic theses; Thèses et écrits académiques.